2020
DOI: 10.3390/vaccines8040600
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Influenza Vaccination among Staff of Nursing Homes According to Behavioral Insights: Analyzing the Choice Architecture during a Nudge-Based Intervention

Abstract: (1) Background: Influenza vaccination uptake in nursing home (NH) workers is uncommon. The aim of this study was to understand the choice architecture of influenza vaccination acceptance or refusal among them and to promote vaccination acceptance using the nudge approach. (2) Methods: In autumn 2019, a nudge intervention with a contextual qualitative analysis of choice architecture of vaccination was performed among the staff of eight Tuscan NHs. In summer 2020, a cross-sectional study including the staff of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(48 citation statements)
references
References 35 publications
0
48
0
Order By: Relevance
“…The survey instrument used in this study consisted of 52 items related to vaccine confidence [ 23 ], vaccine literacy [ 24 ], multilevel-theory-model-based initiation of vaccination behavior [ 25 , 26 ], and demographic questions. Vaccine literacy instruments (14 items) include functional (5 items), iterative or communicative (5 items), and critical literacy (4 items).…”
Section: Methodsmentioning
confidence: 99%
“…The survey instrument used in this study consisted of 52 items related to vaccine confidence [ 23 ], vaccine literacy [ 24 ], multilevel-theory-model-based initiation of vaccination behavior [ 25 , 26 ], and demographic questions. Vaccine literacy instruments (14 items) include functional (5 items), iterative or communicative (5 items), and critical literacy (4 items).…”
Section: Methodsmentioning
confidence: 99%
“…49 A mixed-methods study in Italy demonstrated that a personalised individual letter significantly increases influenza vaccine intentions among healthcare workers (HCWs) who received the nudge intervention compared with the control group. 50 An RCT in the USA showed that sending reminder postcards to elderly adults who were late for at least one vaccine significantly increases vaccination rates. 51 On the other hand, using the same approach in terms of frequency and nature of reminders, an RCT in a large acute care hospital in the UK found no evidence that influenza vaccine uptake is affected by reminder letters.…”
Section: Make Available Information Salientmentioning
confidence: 99%
“…Open only about their professional responsibility but also the personal working burden the staff would have to deal with in cases of colleagues getting sick. Unlike Schmidtke et al, 30 Lorini et al 31 found a significant effect in the intervention group regarding the intention to get the influenza vaccine, which increased from 2018 to 2019 and 2020.…”
Section: Dos Santos Et Al 37mentioning
confidence: 72%
“…That said, HCPs might now have a much different emotional and cognitive response to COVID-19 than influenza, and new intervention strategies should be investigated. The significant positive results found by Lorini et al 31 could for instance be due to the already large impact of COVID-19 affecting inclination towards vaccination among HCPs. Other studies have shown vaccine hesitancy among skilled nursing facility staff regarding the COVID-19 vaccine, either because of the development and testing or personal fears of getting sick.…”
Section: Nudging Vaccinationmentioning
confidence: 91%
See 1 more Smart Citation